The Effectiveness of Hand Muppet Learning Media Based on Local Wisdom to Improve Cultural Literacy and Citizenship Ability - Laila, Alfi; Pitoyo, Andri; Sukasih, Sri; Baharudin, Baharudin (Department of Special Education, 2023)
A nation with high cultural literacy describes the competence of its citizens who can think critically, creatively and communicatively in the face of global competition. The main problem of this research is the low level of cultural literacy and citizenship skills of elementary school students. One of the causes of these problems is the low quality of the learning media used in learning in elementary schools. This study aims to describe the effectiveness of using hand muppet learning media based on local wisdom and the impact of using hand muppet learning media on increasing cultural literacy skills and citizenship of elementary school students. The research model used is a combination method of an exploratory type. The sample of this research is elementary school students in six Kediri elementary schools who have different characteristics. Based on the research results, it was found that the hand muppet was learning media based on local wisdom that was developed and contributed to increasing the ability of cultural literacy and citizenship. This ability improvement occurred throughout the sample schools. Thus, the hand muppet learning media based on local wisdom functions for students with high and low competence.